Diary of an Ordinary Woman - Margaret Forster (London, United Kingdom Vintage Publishing, 2004)
Margaret Forster presents the 'edited' diary of a woman, born in 1901, whose life spans the twentieth century. On the eve of the Great War, Millicent King begins to keep her journal and vividly records the dramas of everyday life in a family touched by war, tragedy, and money troubles. From bohemian London to Rome in the 1920s her story moves on to social work and the build-up to another war, in which she drives ambulances through the bombed streets of London. Here is twentieth-century woman in close-up coping with the tragedies and upheavals of women's lives from WWI to Greenham Common and beyond. A triumph of resolution and evocation, this is a beautifully observed story of an ordinary woman's life - a narrative where every word rings true.
Keywords: War -- War